DETERMINANTS OF FINANCIAL INCLUSION INFORMATION DISCLOSURE OF SHARIA COMMERCIAL BANKS IN INDONESIA - Ahmad Shofiy Mubarok; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh ukuran bank, reputasi, profitabilitas, aktivitas sosial terhadap pengungkapan informasi inklusi keuangan pada bank umum syariah di Indonesia periode 2015-2019 secara parsial dan simultan. Penelitian ini menggunakan metode kuantitatif dengan teknik analisis regresi data panel menggunakan alat penelitian Eviews 10. Hasil penelitan ini menunjukkan bahwa secara parsial, variabel ukuran bank, reputasi, aktivitas sosial berpengaruh positif signifikan terhadap pengungkapan informasi inklusi keuangan. sedangkan profitabilitas berpengaruh negatif signifikan terhadap pengungkapan informasi inklusi keuangan. Secara simultan, variabel ukuran bank, reputasi, profitabilitas, aktivitas sosial berpengaruh positif signifikan terhadap pengungkapan informasi inklusi keuangan pada bank umum syariah di Indonesia periode 2015-2019.  Kata Kunci: Ukuran bank, reputasi, profitabilitas, aktivitas sosial, pengungkapan informasi inklusi keuangan. ABSTRACTThis study aims to determine the effect of bank size, reputation, profitability, social activity on financial inclusion information disclosure of sharia commercial banks in Indonesia from 2015 to 2019 partially and simultaneously. This study uses a quantitative method with panel data regression analysis with Eviews 10. The results of this study indicate that partially, the variables of bank size, reputation, social activity have a significant positive effect on financial inclusion information disclosure. While profitability has a significant negative effect on financial inclusion information disclosure. Simultaneously, the variables of bank size, reputation, profitability, social activity have a significant positive effect on financial inclusion information disclosure of sharia commercial banks in Indonesia from 2015 to 2019.Keywords: bank size, reputation, profitability, social activity, financial inclusion information disclosure. DAFTAR PUSTAKAAlderfer, C. P. (1969). An empirical test of a new theory of human needs. Organizational Behavior and Human Performance, 4(2), 142–175. https://doi.org/10.1016/0030-5073(69)90004-XAryska, M. (2017). Pengaruh reputasi perusahaan dan kualitas pelayanan terhadap kepuasan pasien (Kasus rumah sakit islam ibnu sina Pekanbaru). Journal of Chemical Information and Modeling, 53(9), 1689–1699.Ascarya, A., Tanjung, H., & Rahmawati, S. (2016). Design and determine holistic financial inclusion index for baitul maal wat tamwil. 2nd International Conference on IPAFEM, August. https://www.researchgate.net/publication/312494768Asrarsani. (2013). Pengaruh karakteristik perusahaan terhadap pengungkapan CSR pada perusahaan perbankan yang tercatat di bursa efek Indonesia. Skripsi tidak dipublikasikan. Makassar: Universitas Hasanuddin.Bose, S., Bhattacharyya, A., & Islam, S. (2017). Dynamics of firm-level financial inclusion: Empirical evidence from an emerging economy. Journal of Banking and Finance Law and Practice, 27 (1), 47-68.Chehade et al. (2017). Financial inclusion measurement in the Arab world. United Arab Emirates: Arab Monetary Fund.Ching, H. Y., & Gerab, F. (2017). Sustainability reports in Brazil through the lens of signaling, legitimacy and stakeholder theories. Social Responsibility Journal, 13(1), 95–110. https://doi.org/10.1108/SRJ-10-2015-0147Fitriana, N. L., & Prastiwi, A. (2014). Faktor-faktor yang mempengaruhi luas pengungkapan sukarela dalam annual report. Diponegoro Journal of Accounting, 3(3), 642-651.Ginting, A. N. (2012). Analisis faktor-faktor yang mempengaruhi tingkat pengungkapan sukarela dalam laporan tahunan perusahaan manufaktur di Indonesia. Skripsi tidak dipublikasikan. Depok: Universitas Indonesia.Grund, N. E. (1996). Reputation: Realizing value from the corporate image. Academy of Management Perspectives, 10(1), 99–101. https://doi.org/10.5465/ame.1996.9603293245Haldar, P. K., Rahman, S. M. M., Mia, S., Ahmed, F., & Bashawir, A. (2016). Assessing the Role of Corporate Social Responsibility Practices of Commercial Banks in Enhancing Financial Inclusion : A Study on Banking Sector in Bangladesh. International Journal of Economics and Financial Issues, 6(4), 1778–1783.Hossain, M., & Hammami, H. (2009). Advances in accounting, incorporating advances in international accounting voluntary disclosure in the annual reports of an emerging country: The case of Qatar. Advances in Accounting, 25(2), 255–265. https://doi.org/10.1016/j.adiac.2009.08.002OJK. (2016). Peraturan OJK No.76/POJK.07/2016.OJK. (2019). Siaran Pers Survei OJK 2019: Indeks literasi dan inklusi keuangan meningkat. Sp 58/Dhms/Ojk/Xi/2019, November, 1.Rahmawati. (2020). Financial inclusion disclosure in Islamic microfinance: The case of baitul mal wa tamwil. Enhancing Financial Inclusion, II, 137–160. Diakses dari https://link.springer.com/chapter/10.1007/978-3-030-39939-9_5Ramzan, M., Amin, M., & Abbas, M. (2021). How does corporate social responsibility affect financial performance, financial stability, and financial inclusion in the banking sector? Evidence from Pakistan. Research in International Business and Finance, 55(August 2020), 1-9. https://doi.org/10.1016/j.ribaf.2020.101314Sharma, N. (2014). Advances in accounting, incorporating advances in international accounting extent of corporate governance disclosure by banks and finance companies listed on Nepal stock exchange. Advances in Accounting, 30(2), 425-439. https://doi.org/10.1016/j.adiac.2014.09.014Siyoto, S., & Sodik, M. A. (2018). Dasar metodologi penelitian. Jakarta: Literasi Media Publishing.Ullah. (2015). Corporate Social Responsibility Practices in the Banking Sector in Bangladesh - An Assessment. Bank Parikrama, 38(3&4), 129-152.